Togo : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Third Review Under the Poverty Reduction and Growth Facility (PRGF) for Togo. The PRGF-supported program remains on track despite the shocks. All quantitative and structural performance criteria through end-June 2009 were met. All targets for implementation of structural reforms were fulfilled through end-June; delays have developed for the second half of 2009 primarily owing to capacity constraints. The authorities have committed to completing key reforms in 2010 to strengthen public finances, restructure the banking system, and accelerate growth.